Pendidikan Islam Mesir dan Pengaruhnya Terhadap Pendidikan Islam Indonesia - Ilham Barita Siregar; Salmiwati (Jurnal Pendidikan Islam, 2022)
Egypt is a very dynamic country in the association of knowledge so that many students from various parts of the world are very interested in its academic atmosphere. The history of education in Egypt, especially Al-Azhar, has a relationship with the dynamics of Islamic diversity in the country, it can be seen from the gait of its alumni who have filled and developed science that covers all aspects of social, political, cultural and religious life. Thus, it is necessary to deepen the Islamic education in Egypt which affects Islamic education in Indonesia. The purpose of this article is to explore the influence of Islamic education in Egypt on Islamic education in Indonesia. The research method in this article uses the literature study method. Data was collected through the results of library searches and the results of relevant studies followed by content analysis. The results showed that Egypt became an important country as a reference in developing and providing direction for the modernization movement of Islamic education and Muslim countries. The Indonesian Ministry of Religion tends to make Egypt a role model for the development of modern Islamic education and universities in Indonesia. The educational format of Al Azhar University is almost entirely used as a model for the development of study programs and faculties in all IAIN and UIN in Indonesia. After Indonesia entered the reformation, several IAINs in Indonesia were upgraded to become Indonesian Islamic University. Since then, UIN has started to develop the faculty of medicine and health.